Montreal Museum of Fine Arts, collection of Mediterranean antiquities =Musée des beaux-arts de Montréal, collection des antiquités méditerranéennes. Volume 2, The terracotta collection - Zoïtopoúlou, Eléni P. (Monumenta Graeca et Romana, 2010)
This catalogue raisonné describes the lamps and statuettes in terracotta of the Montreal Museum of Fine Arts, to which are added two lamps made of bronze. The collection, small but eclectic, has mostly been assembled in recent years and represents a wide variety of types in these two categories. After an introduction discussing the techniques involved in the production of these objects, the catalogue proper presents 44 lamps, 21 figurines and a single arula with full illustration. This catalogue makes the collection available to a wide readership: students, curators, archaeologists, art historians, collectors and everybody with serious interest in the material culture of the ancient world. This is the second volume of a series intended to make public the different parts of the museum's collection of Mediterranean antiquities. Ce catalogue raisonné présente les lampes et les figurines en terre cuite du Musée des beaux-arts de Montréal ainsi que deux lampes de bronze. La collection, petite mais éclectique, a été formée récemment et comprend un bon échantillon de ces types d'objets. Après en avoir expliqué les techniques de fabrication, le catalogue illustré décrit 44 lampes, 21 statuettes et une arula . Ce livre s'adresse aux étudiants, aux conservateurs, aux archéologues, aux historiens d'art et aux collectionneurs, bref à ceux qu'intéresse l'archéologie du monde antique. Il s'agit du deuxième catalogue d'une série qui vise à publier la collection des antiquités du Musée.